Coherent Phonon‐Induced Gigahertz Optical Birefringence and Its Manipulation in SrTiO3. Issue 7 (16th January 2023) - Sun, Tao; Zhou, Chun; Guo, Hongli; Meng, Zhi; Liu, Xinyu; Wang, Zhou; Zhou, Han; Fei, Yuming; Qiu, Kang; Zhang, Fapei; Li, Bolin; Zhu, Xuetao; et al.
Abstract: Birefringence, which modulates the polarization of electromagnetic wave, has been commercially developed and widely used in modern photonics. Fostered by high‐frequency signal processing and communications, feasible birefringence technologies operating in gigahertz (GHz) range are highly desired. Here, a coherent phonon‐induced GHz optical birefringence and its manipulation in SrTiO3 (STO) crystals are demonsrated. With ultrafast laser pumping, the coherent acoustic phonons with low damping are created in the transducer/STO structures. A series of transducer layers are examined and the optimized one with relatively high photon–phonon conversion efficiency, i.e., semiconducting LaRhO3 film, is obtained. The most intriguing finding here is that, by virtue of high sensitivity to strain perturbation of STO, GHz optical birefringence can be induced by the coherent acoustic phonons and the birefringent amplitudes possess crystal orientation dependence. Optical manipulation of both coherent phonons and its induced GHz birefringence by double pump technique are also realized. These findings reveal an alternative mechanism of ultrafast optical birefringence control, and offer prospects for applications in high‐frequency acoustic‐optics devices. Abstract : To address the challenge of high‐frequency signal processing, a gigahertz (GHz) optical birefringence has been developed here. With ultrafast laser pumping, the coherent acoustic phonons with low damping are created in the transducer/SrTiO3 . By virtue of high sensitivity to strain, GHz optical birefringence is induced subsequently in SrTiO3 and it can also be effectively modulated by optical pumping.